Processable high internal phase Pickering emulsions using depletion attraction - Kim, KyuHan; Kim, Subeen; Ryu, Jiheun; Jeon, Jiyoon; Jang, Se Gyu; Kim, Hyunjun; Gweon, Dae-Gab; Im, Won Bin; Han, Yosep; Kim, Hyunjung; Choi, Siyoung Q. (Nature Publishing Group, 2017)
High internal phase emulsions have been widely used as templates for various porous materials, but special strategies are required to form, in particular, particle-covered ones that have been more difficult to obtain. Here, we report a versatile strategy to produce a stable high internal phase Pickering emulsion by exploiting a depletion interaction between an emulsion droplet and a particle using water-soluble polymers as a depletant. This attractive interaction facilitating the adsorption of particles onto the droplet interface and simultaneously suppressing desorption once adsorbed. This technique can be universally applied to nearly any kind of particle to stabilize an interface with the help of various non-or weakly adsorbing polymers as a depletant, which can be solidified to provide porous materials for many applications.